1999
DOI: 10.1207/s15327752jpa7303_4
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Alexithymia and the Five-Factor Model of Personality: A Facet-Level Analysis

Abstract: The relation between alexithymia and both the domain and the facet level of the five-factor model (FFM) of personality was examined in a sample of 101 university students by using the Twenty-Item Toronto Alexithymia Scale (TAS-20; Bagby, Taylor, & Parker, 1994) and the Revised NEO Personality Inventory (Costa & McCrae, 1992c). Consistent with the alexithymia construct, the TAS-20 was positively correlated with Neuroticism (N) and negatively correlated with Extraversion (E) and Openness (O), whereas no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
93
2
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 35 publications
20
93
2
8
Order By: Relevance
“…Similarly, our results that high levels of alexithymia are associated with high levels of Neuroticism and low levels of Extraversion and Openness are consistent with previous work. For example, Neuroticism was found to be negatively correlated with alexithymia particularly with the facets of anxiety, depression, self-consciousness and vulnerability (Bagby et al, 1994;Luminet et al, 1999), and Extraversion (Wise et al, 1992) and Openness were found to negatively correlate with alexithymia (Bagby et al, 1994;Luminet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results that high levels of alexithymia are associated with high levels of Neuroticism and low levels of Extraversion and Openness are consistent with previous work. For example, Neuroticism was found to be negatively correlated with alexithymia particularly with the facets of anxiety, depression, self-consciousness and vulnerability (Bagby et al, 1994;Luminet et al, 1999), and Extraversion (Wise et al, 1992) and Openness were found to negatively correlate with alexithymia (Bagby et al, 1994;Luminet et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…11 This finding supported the idea that alexithymia is a construct associated with distinct personality dimensions. [16][17][18]37 Several studies have shown that alexithymia is multidimensional rather than unidimensional, consisting of emotional and cognitive components. 29,38 The emotional component is characterized by an incapacity to describe and identify feelings, and the cognitive component is characterized by a lack of daydreaming and the presence of externally oriented thinking.…”
Section: Discussionmentioning
confidence: 99%
“…16 Other correlational studies also confirmed these relationships. [16][17][18][19][20] Wise et al suggested that alexithymia is a unique personality trait that is not fully explained by the NEO-Five-Factor Inventory (NEO-FFI). 18 A recent study found a moderate positive correlation between TAS-20 total score and neuroticism, but weak but significant negative correlations with openness to experience and conscientiousness domains of the NEO-FFI.…”
mentioning
confidence: 99%
“…A study of the Big Five personality dimensions found that high neuroticism, low extraversion, and low openness-but not agreeableness or conscientiousnesswere associated with alexithymia, and specific facets within these dimensions accounted for these associations (Luminet, Bagby, Wagner, Taylor, & Parker, 1999). Other research has supported these findings (Zimmermann, Rossier, Meyer de Stadelhofen, & Gaillard, 2005).…”
Section: Is Alexithymia a Unique Psychological Construct?mentioning
confidence: 96%